Investigation of the effects of tadalafil and telmisartan in bleomycin-induced pulmonary fibrosis on rats - Kazaz, İlke Onur and Özgür, Güner Kemal and Çobanoğlu, Ümit and Kalyoncu, Nuri İhsan and Karagüzel, Ersagun and Topbaş, Murat and Eren, Hüseyin and Kazaz, Seher Nazlı and Özyavuz, Rasin (Journal of Surgery and Medicine, 2020)
Aim: Pulmonary toxicity related to bleomycin, an antitumor drug used in the treatment of several malignancies, is a challenge, and studies to find out molecules to prevent it are ongoing. In this study, we aimed to investigate the effectiveness of telmisartan and tadalafil in an experimental rat model of bleomycin-induced lung fibrosis. Methods: A total of 32 male rats were divided into four groups: Control group, Bleomycin group, Bleomycin-plus-Tadalafil group and Bleomycin-plus-Telmisartan group. Lung fibrosis was achieved by intratracheal administration of bleomycin, and the same procedure was performed to the control group, but saline was substituted for bleomycin. Tadalafil and telmisartan were administered with an orogastric catheter for 14 days. Tissue malondialdehyde levels (MDA) were determined using colorimetric methods. Masson’s trichrome staining was used in the histological examination of the tissue samples. Results: The fibrosis scores of bleomycin-plus-tadalafil and bleomycin-plus-telmisartan groups were lower than that of the bleomycin group (P=0.007 and P=0.007, respectively). MDA levels did not differ among study groups. Conclusion: Tadalafil and telmisartan were found to decrease fibrosis scores, which were increased with bleomycin, concluding that pulmonary toxicity was related to multiple processes and preventable.